Mazal tov, amigos! : Jews and popular music in the Americas - Ran, Amalia; Morad, Moshe (Jewish Latin America (Leiden, Netherlands), 2016)
Winner of the Jewish Music Special Interest Group Paper Prize of 2018 Mazal Tov, Amigos! Jews and Popular Music in the Americas seeks to explore the sphere of Jews and Jewishness in the popular music arena in the Americas. It offers a wide-ranging review of new and old trends from an interdisciplinary standpoint, including history, musicology, ethnomusicology, ethnic studies, cultural studies, and even Queer studies. The contribution of Jews to the development of the music industry in the United States, Argentina, or Brazil cannot be measured on a single scale. Hence, these essays seek to explore the sphere of Jews and popular music in the Americas and their multiple significances, celebrating the contribution of Jewish musicians and Jewishness to the development of new musical genres and ideas.